Mifologičeskaja sostavljajuščaja slavjanskoj ihtiologičeskoj terminologiiMythological Component in the Slavic Ichthyological Terminology - Razauskas, Dainius (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author discusses the Slavic ichthyological terminology which is either directly connected with some well-known mythological beings or indicates a mythological imagery scarcely characteristic to common living conditions of fi sh. Such ichthyonyms are explained according to the appearance of the fish and its behaviour. Nevertheless, in some cases, semantics of these ichthyonyms conforms to a corresponding mythological motives so well that the influence of mythological world-view on their origin is undoubted.